A new modeling method for S‐MCSRM driven by three‐phase full bridge converter. (2014) - ,; ,; ,; ,; ,
Abstract : Purpose – The S‐MCSRM is a two‐phase excited switched reluctance motor (SRM), with the short flux path and mutual inductance coupling, which is suitable for the oil submersible pump application owing to large torque and three‐wire connection with the standard full‐bridge power converter. However, there is not literature to disclose its model due to the complicated mutual inductance coupling. The FEM model is a time‐consuming method to analyze this motor. For the first time, this paper aims to propose an S‐MCSRM model for performance analysis and control method developing. The proposed model would save simulation time and be a theoretical fundamental for further implementing control algorithm.Design/methodology/approach – The S‐MCSRM's operating principle is analyzed, and the voltage equation and the generated torque are deduced. The FEM is utilized to obtain the five typical magnetization curves that describe the S‐MCSRM's magnetic path characteristic. The magnetic co‐energy equation, phase torque and total torque equations are obtained. From the basic voltage equation, the S‐MCSRM's state space model is built for the dynamic analysis and control purpose. The S‐MCSRM is widely analyzed in detail by using the proposed model and comparison with the conventional SRM. JMAG finite element package is used to verify the proposed model.Findings – The proposed modeling method is validated by the identical results to those from FEM‐based JMAG software. The proposed model just takes second‐level time, which is far less than minute‐level time consuming of FEM method. The S‐MCSRM generates larger torque than the conventional SRM, with three‐wire and standard full bridge power converter, and it is confirmed that the S‐MCSRM is suitable for the oil submersible pump applications.Originality/value – This paper proposes a new modeling method for the S‐MCSRM to exactly analyze the motor's operating performances, and also it is a theoretical fundamental for developing control algorithm. The proposed model saves much time in analysis, calculation, and simulation, when compared to the FEM method. The completed analysis including flux linkages, torque, torque‐ripple, and torque‐speed characteristic discloses the S‐MCSRM's steady‐state operating performances, which provides the deep insight for this kind of motor's applications.